"A Road to Peace and Freedom" The International Workers Order and the Struggle for Economic Justice and Civil Rights, 1930-1954 - Zecker, Robert (Temple University Press, 2018)
Zecker examines the multicultural civil-rights activism and union militancy of the International Workers Order and other left-leaning immigrant groups, investigating the program of such organizations regarding civil rights, unionizing, and workplace justice. It looks at what these organizations did that caused the U.S. government to prosecute them and how these groups sought to defend themselves and maintain a Popular Front coalition of progressives in the face of the rapidly developing call for Cold War conformity. The suppressions of dissent narrowed the degree of progress on economic justice and racial civil rights in America for decades to come, and the author argues that the story of the IWO's demise has relevance for 21st century America's narrowed range of critiques of government policy and unequal racial and economic status quo.